Israel : Staff Report for the 1999 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Israel is on the threshold of a marked improvement in economic performance. Passage of a revised Bank of Israel law along the lines recommended by the Levin Commission and endorsed by the Bank of Israel should be achieved as soon as possible. Continued vigilance regarding real exchange rate trends, conditions of access to international capital markets, and the health of the banking sector is essential. The government is to be commended for its success in liberalizing Israel's foreign trade and capital accounts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet